Financing of the 2030 Agenda and financial cooperation: a note about Spain - Alonso, José Antonio (Revista Española de Desarrollo y Cooperación, 2023)
The article aims to discuss the financial resources needed for making the 2030 Agenda a reality. In this context, the potentiality of financial cooperation is explored, taking into account particularly those instruments oriented to support private sector involvement in the development process. The article finishes with a brief note on the institutional design of the financial cooperation in Spain.